PENYIDIKAN PELAKU TINDAK PIDANA PENCURIAN MOTOR DISERTAI KEKERASAN DI WILAYAH HUKUM KEPOLISIAN SEKTOR TAMPAN - Anugrah, Roby; Effendi, Erdianto; Edorita, Widia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2017)
Theft is a crime that ofthen occur and cause unrest in society, which is all the inconvenieces that have an impact on security and order in society. Motorcycle is a menas of transport fovored by today society, with the many motorcycle that exist is district of Tampan Pekanbaru city made motorcycle as one of the objects of theft by perpetrators, not just simply steal the motorcycle, sometimes the perpetrators of crime committed violence againts the victim in theft of motorcycle.The purpose of thesis, which determine the extent of the interrogation of criminal motorcycle theft with violence in the district of charming town of pekanbaru, the obstacles faced in the process of criminal investigation motorcycle theft with violence as well as efforts in the face of these obstacles.This type of research can be classified in this type of sociological juridical research, because this research author direcly conduct research on the location or point examited. This research was conduted in police sector Tampan Pekanbaru City, While the sample population is overlall the parties relating to the issue examited in this study, the data source used, primary data, secondary data and data tertiary, data collection tehcniques in this study with interviews and literature study.From the result of research by three formulation of the problem, there are three main things tat can be inferres, first to the criminal investigation process motorcycle theft with violence commited by the police sector Tampan where a high rate of motorcycle theft with violence that has not been revealed. Both barries faces by the sector police Tampan in uncovering cases of motorcycle theft with violence is in terms of the offender and the community aspect. Third efforts are being made to overcome these barries is in terms of the police and the police and the community aspect.Keywords : Investigation-Actors-Theft Motor With Violence